The cities book : a journey through 86 of the world's greatest cities - Carswell, Heather (Lonely Planet kids., 2016)
"This book is jam-packed with pictures, facts, and stats about a host of incredible cities-- from Auckland, Beijing, and Copenhagen all the way to Zanzibar Town"--Page 4 of cover.